Peningkatan Keterampilan Komunikasi Peserta Didik Melalui Model Pembelajaran Icare Pada Materi Sistem Koloid - Wulandari Wulandari; Susilawati Susilawati; Maria Erna; Phadilah Ismayanti Nasution (Universitas Negeri Padang, 2026)
This study aims to analyze the effectiveness of the ICARE learning model in improving students’communication skills on colloidal systems. This study uses a quantitative, quasi-experimental design with a nonequivalent control group. The research sample consisted of two XI MIPA classes at SMAN 1 Pekanbaru: the experimental class, which used the ICARE model, and the control class, which used conventional learning. Communication skills data were collected through observation sheets, while improvements in learning outcomes were analyzed using the N-Gain value. The results showed that applying the ICARE learning model improved students' communication skills, with moderate to high gains. In addition, there was a significant difference between the experimental and control classes. These findings indicate that the ICARE learning model is an effective alternative for developing students' communication skills in colloidal systems.